Síndrome del quemado como predictor del compromiso laboral en docentes de universidades de Chiclayo, Perú - Gamarra Moncayo, José Rolando (Universidad de Costa Rica, 2024)
In an increasingly dynamic and complex world, the professional figure of teachers who show commitment to their work acquires fundamental importance in quality education. In this sense, this research aims to analyze burnout syndrome as a predictor of work commitment in teachers of private universities in the city of Chiclayo, Peru, in a context of mitigation of the COVID-19 pandemic. This is an empirical study of cross-sectional predictive design. The final sample included 100 undergraduate teachers, of both sexes, whose ages ranged from 35 to 60 years (M=46.63; SD=9.90). The instruments applied were the Burnout Syndrome Scale version for teachers and the Utrecht Work Engagement Scale, virtualized in Google Forms. The data collected were subjected to simple regression analysis, also reporting effect size indices and statistical power, to ensure greater scope and precision in the results. Low levels of burnout syndrome and high levels of work engagement were reported; moreover, burnout syndrome negatively and significantly predicted work engagement and its dimensions of vigor and dedication; not so for absorption. Therefore, the reported findings suggest that burnout syndrome can predict work engagement and its factors, except for absorption, in teachers of private universities in Chiclayo. The limitations and practical implications of the study are discussed.